The impact of acquisitions on company performance: evidence from data of U.K. pharmaceutical Firms - Xiong, Tian (2013)
M&A is carried out to obtain other legal entity’s property right for a certain economic realization, often to share costs, increase efficiency or gain market power. Mergers and acquisitions, well known for its short form M&A, is an important means of business expansion; it is also often used as a tool to avoid certain regulations or laws, e.g., the monopoly and the tax laws (Ross, et al., 2002). Over past ten years, there has been a great deal of cross-border M&A activity involving UK companies. However, domestic and cross-border mergers and acquisitions between UK companies were decreased every year since 2007. In addition, previous studies have revealed a critical finding for companies and shareholders that about 60 to 80 percent of M&A activities did not actually produce any value (Mehmood, 2009). Some researchers also found that mergers can bring large benefits for shareholders of targeted company by using event and accounting study. This study attempts to find out the effect of M&A in UK pharmaceutical firms’ performance. We use the database provided by FAME for the period of 2003-2013. There are two main accounting study methods are applied; cross-sectional analysis and panel analysis. Cross-sectional tried to figure out whether there is difference of profitability between merged and unmerged. Panel analysis is applied to compare the profitability of firms before and after acquisition. After controlling other possible influencing factors, the results of two regression analysis both suggest that M&A activity have no effect on firm’s performance. As a result, contrary to common beliefs and expectations, we conclude that mergers usually do not lead to improve the acquirer's financial performance.